Peningkatan kecerdasan emosional guru melalui program psikoedukasi - Yuli Asmi Rozali; Ratnawati Susanto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
Education is the most important sector. In the law, it is written that teachers must have four competencies, namely pedagogic competence, personality competence, social competence, and professional competence obtained through professional education. So it is important for a teacher to have sensitivity or empathy in carrying out his role as an educator is called emotional intelligence. The characteristics of the teachers are the teachers in the Kebon Jeruk and Grogol Petamburan sub-districts, West Jakarta, totaling 28 teachers, the one group pretest-posttest design. Based on the results of data processing using statistical analysis tests categorizing the level of emotional intelligence of teachers the results is that the number of teachers who have a level of emotional intelligence has increased, amounting to 89% while previously teachers who had a high level of emotional intelligence were less than 75% (< 75%). The results of teacher interviews also revealed that more than 75% (≥75%) stated that the community service program was effective in improving the emotional intelligence of teachers, with an effective level of 75% and there were 11% of teachers who still had low emotional intelligence